(untitled) (Journal of Hama University, 2024)
The current research seeks to test the effect of earnings management (accounting accrual basis) on the stock returns of companies and banks that practice earnings management and are listed on the Damascus Stock Exchange. The study sample included (17) companies and banks listed on the Damascus Stock Exchange, during the period from the first quarter of the year (2013) to the fourth quarter of the year (2019). In order to achieve the objective of the study, the Modified Jones 1995 model was initially applied to identify companies and banks practicing earnings management, which numbered (4) companies and two banks, and to test the impact of earnings management practices on the returns of the shares of the practicing companies, a standard study based on the Augmented ARDL model was relied on for quarterly panel data, the results of which concluded that there is no effect of earnings management (on an accrual basis) on stock returns in the short and long terms.